BRCA1 185delAG Mutation Enhances Interleukin-1β Expression in Ovarian Surface Epithelial Cells. (19th August 2015) - Woolery, Kamisha T.; Mohamed, Mai; Linger, Rebecca J.; Dobrinski, Kimberly P.; Roman, Jesse; Kruk, Patricia A.
Abstract : Familial history remains the strongest risk factor for developing ovarian cancer (OC) and is associated with germline BRCA1 mutations, such as the 185delAG founder mutation. We sought to determine whether normal human ovarian surface epithelial (OSE) cells expressing the BRCA1 185delAG mutant, BRAT, could promote an inflammatory phenotype by investigating its impact on expression of the proinflammatory cytokine, Interleukin-1 β (IL-1 β ). Cultured OSE cells with and without BRAT were analyzed for differential target gene expression by real-time PCR, western blot, ELISA, luciferase reporter, and siRNA assays. We found that BRAT cells expressed increased cellular and secreted levels of active IL-1 β . BRAT-expressing OSE cells exhibited 3-fold enhanced IL-1 β mRNA expression, transcriptionally regulated, in part, through CREB sites within the (−1800) to (−900) region of its promoter. In addition to transcriptional regulation, BRAT-mediated IL-1 β expression appears dualistic through enhanced inflammasome-mediated caspase-1 cleavage and activation of IL-1 β . Further investigation is warranted to elucidate the molecular mechanism(s) of BRAT-mediated IL-1 β expression since increased IL-1 β expression may represent an early step contributing to OC.